Bioactive Ion‐Based Switchable Supercapacitors. Issue 50 (15th November 2022) - Li, Panlong; Bräuniger, Yannik; Kunigkeit, Jonas; Zhou, Hanfeng; Ortega Vega, Maria Rita; Zhang, En; Grothe, Julia; Brunner, Eike; Kaskel, Stefan
Abstract: Switchable supercapacitors (SCs) enable a reversible electrically‐driven uptake/release of bioactive ions by polarizing porous carbon electrodes. Herein we demonstrate the first example of a bioactive ion‐based switchable supercapacitor. Based on choline chloride and porous carbons we unravel the mechanism of physisorption vs. electrosorption by nuclear magnetic resonance, Raman, and impedance spectroscopy. Weak physisorption facilitates electrically‐driven electrolyte depletion enabling the controllable uptake/release of electrolyte ions. A new 4‐terminal device is proposed, with a main capacitor and a detective capacitor for monitoring bioactive ion adsorption in situ . Ion‐concentration control in printed choline‐based switchable SCs realizes switching down to 8.3 % residual capacitance. The exploration of adsorption mechanisms in printable microdevices will open an avenue of manipulating bioactive ions for the application of drug delivery, neuromodulation, or neuromorphic devices. Abstract : Inspired by the highly efficient information transmission of biologically active compounds in nerve systems, a well‐controllable capture/release of biologically active ions is achieved by a switchable supercapacitor.